Use of Recombinant Human Bone Morphogenetic Protein-2 With Iliac Crest Bone Graft Instead of Iliac Crest Bone Graft Alone in Lumbar Spondylolysis. Issue 2 (March 2022) - Meng, Hao; Gao, Yuan; Zhao, Guangmin; Sun, Tiansheng; Li, Fang
Abstract : Study Design: A retrospective study. Objective: The aim of this study was to evaluate the clinical and radiographic effect of recombinant human bone morphogenetic protein-2 (rhBMP-2) in pars repair of lumbar spondylolysis. Summary of Background Data: BMP-2 is a growth factor that plays a role in the formation of bone and promotes bone healing. However, few studies of using rhBMP-2 in pars repair have been reported. Methods: Direct pars repair and pedicle screw fixation was performed, which were added with 1 mg of rhBMP-2 and iliac crest bone graft in the study group (rhBMP-2 group, n=32) and iliac crest bone graft alone in the autograft group (n=36). Patients completed the visual analog scale and the Oswestry Disability Index preoperation, 3, 6, and 12 months after the operation. Computed tomography scans with axial and sagittal reconstructions were performed at 6, 9, 12, 18, and 24 months postoperatively. Results: Baseline demographic data showed no significant difference between 2 groups. There were significant differences for the Oswestry Disability Index score at 3 and 6 months postoperatively, which were higher in the autograft group. There was no significant difference between the groups with respect to the overall union status. As for union speed, the trabecular bone appeared earlier and union rates were higher in rhBMP-2 group than in the autograft group at 9, and 12 months postoperatively. No complications were identified in either group. One case in the rhBMP-2 group and 2 cases in the autograft group underwent revision surgery. Conclusion: Compared with iliac crest bone graft alone, the use of rhBMP-2 can accelerate fusion in pars repair for young patients with spondylolysis. The union rates were significantly different at 9 and 12 months after surgery. This study showed no clinical difference when adding rhBMP-2 compared with iliac crest bone graft alone.